2021
DOI: 10.3389/fpubh.2021.661517
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment to Enable Recovery of the Homeless: The HOP-TR Study

Abstract: Background: Homelessness is an increasing problem in Western European countries. In the Netherlands, policy reforms and austerity measures induced an urgent need for management information on local homeless citizens. Municipal authorities initiated cross-sectional reviews of Homeless Service (HS) users. The resulting Homeless People Treatment and Recovery (HOP-TR) study developed a health and needs assessment strategy over different domains to comprehensively assess individuals and care networks with the persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Thus, despite the fact that this population is known to experience a disproportionate amount of stressors relative to the domiciled population [45] and exhibit high rates of mental and physical health conditions [3][4][5][6][7][8][9], interventions designed to foster social support for individuals experiencing homelessness may benefit their overall experience of physical and/or mental health. Consistent with a recovery-oriented approach to the care of individuals experiencing homelessness, results suggest the potential importance of assessing the capability of the multi-level ecological networks surrounding these adults to assist in their weathering of stressors so that any gaps can be addressed in holistic resiliency building [46]. Thus, interventions to bolster social support for this marginalized group can and should be considered across multiple levels, including those directed at individuals, agencies, and systems that are frequently encountered by this group.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, despite the fact that this population is known to experience a disproportionate amount of stressors relative to the domiciled population [45] and exhibit high rates of mental and physical health conditions [3][4][5][6][7][8][9], interventions designed to foster social support for individuals experiencing homelessness may benefit their overall experience of physical and/or mental health. Consistent with a recovery-oriented approach to the care of individuals experiencing homelessness, results suggest the potential importance of assessing the capability of the multi-level ecological networks surrounding these adults to assist in their weathering of stressors so that any gaps can be addressed in holistic resiliency building [46]. Thus, interventions to bolster social support for this marginalized group can and should be considered across multiple levels, including those directed at individuals, agencies, and systems that are frequently encountered by this group.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, eight articles reported that the dimensions of PH were part of their qualitative research methods, either during data collection [ 34 , 37 , 52 , 59 , 71 ] or as a framework during data analysis to organise themes based on the various dimensions [ 43 , 52 , 67 , 69 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of variance was conducted, based on the subsample means of health problems, and MHRCN. The methods paper proves that subsample addition was continued until topic saturation was reached [42].…”
Section: Study Design and Recruitmentmentioning
confidence: 87%
“…Instead, substantial improvements require a radical commitment to all ingredients of the ecosystem of care. HSU urgently need comprehensive, integrating, socio-ecological ecosystem strategies that better serve the needs of marginalized populations with interdependent needs [27,42]. A crucial concept, defined in the quintuple aim care outcome model, is health equity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation